Production, purification and characterization of L-Glutaminase from Streptomyces sp. isolated from soil - Savitha S. Desai, Sonal J. Chopra, Basavaraj S. Hungund (Journal of Applied Pharmaceutical Science, 2016)
L-Glutaminase, an amidohydrolase enzyme has been a choice of interest in the treatment of lymphoblastic leukaemia. The present study reports production, purification and characterization of extracellular glutaminase enzyme from Actinomycetes. Screening was performed for twenty Actinomycetes isolates from soil; one isolate (Isolate 2) was finally selected based on the activity of glutaminase (32.5 U/ml).The isolate was identified as Streptomyces sp. Effect of physicochemical factors namely temperature, pH, NaCl concentration, and supplementary carbon & nitrogen sources on the production of L-glutaminase from the Streptomyces sp. was carried out. The enzyme production was found to be optimum with glucose as carbon source (33 U/ml), L-glutamine as nitrogen source (33.1 U/ml), at 7 pH (32.8 U/ml), temperature 30oC (32.4 U/ml) and for 0.1% NaCl concentration (32.5 U/ml). The L-glutaminase produced from Streptomyces sp. was purified by ammonium sulphate precipitation, dialysis method and ion exchange chromatography. After the purification of the enzyme by ion exchange chromatography, it has been purified 46-fold from cell-free extract and yield was 3.25%. Characterization of extracellular L-glutaminase showed that the enzyme shown optimal activity at temperature of 30°C, pH 7, at 2% NaCl and for 0.04M substrate and the Km value was calculated to be 2.8mM and Vmax was 7.57 U/ml. The molecular weight of enzyme as determined by sodium dodecyl sulphate polyacrylamide electrophoresis (SDS-PAGE) was found to be 50 kDa.
Keywords: L-Glutaminase, Actinomycetes, Streptomyces sp, ion exchange chromatography, SDS-PAGE.